SURVEY OF MUSIC-LIBRARY PERSONNEL CHARACTERISTICS, 2009. - CLEVELAND, SUSANNAH; PUENTE, MARK A. (Notes, 2011)
Results from the 2009 MLA Survey of Personnel Characteristics are presented and analyzed. Areas covered include education and training, status and salaries, professional activities, and demographics of MLA members. In each area, comparisons are made to results from the study of the same name conducted in 1997.